Du soutenable à l’insoutenable : le tourisme à Bocas del Toro (Panama). L’impact des logiques nationales et globales dans la déstructuration progressive d’une société d’accueil - Camille Le Masne (Études Caribéennes)
The aim of this article, based on a survey of one month on the archipelago of Bocas del Toro in February 2009, is to assess the changes brought by the advent of tourism on Colon’ island for twenty year. The development of the tourism boom in two phases sufficiently differentiated - that of sustainable tourism, says 1990 to 2002, then second phase with a non-tourism control - allowed us to develop a historical analysis of the relationship between populations and tourism. Our investigation, which focuses on the perceptions of the present inhabitants of the island, has highlighted the actors and their role according to their time of arrival on the island; itself linked to the changeover of a concept of tourism another.